Pre-Service Teacher’ Preparation for Teaching English At School - Deta Amelia; Dian Susyla; Sinarman Jaya; Ririn Putri Ananda (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
This research aims to investigate the pre-service teacher’ preparation for teaching English of English Study Program Students of University of Muhammadiyah Bengkulu. The researcher used a descriptive qualitative method. The subject of the study was all of the students at the sixth semester who enrolled microteaching subject at English program of UMB Bengkulu. The microteaching class was divided into five classes with total students 44. The researcher used interview and observation list as the instruments of the research in this study. The interview guide was constructed from “K to 12 Blended Teaching Preparation” adopted by Graham et al. (2019). The result of this research showed that the pre-service teacher’ preparation for teaching English was good or in high level of preparation. The preservice teachers’ preparations were related to some aspects; (a) Preparation related to the material to be taught; (b) Preparation related to learning media; (c) Preparation related to teaching strategies with the following steps; (d). Preparation related to assessment; (e) Preparation related to the use of ICT tool (computer/laptop); and (f) Preparation related to the mastering of using teaching online platforms (Zoom, Whatsapp, Google Classroom). It is suggested for the preservice teachers to be ready to face another possibility for the next during the pandemic of Covid-19, especially the problems which may come among the teaching and learning accessibility. The preservice teachers are required to be more interacted with the modern technology in order to be able to compete with the development of technology especially in education field. Moreover, further studies are recommended to investigate deeper research related to the preservice teachers preparation in teaching English with large number of sample of research. Keywords : Preservice Teacher, Preparation, Teaching English